Proceedings of the International Conference on Ubiquitous Computing & Ambient Intelligence (UCAmI 2022) - Bravo, José; Ochoa, Sergio; Favela, Jesús (Lecture Notes in Networks and Systems, 2023)
XXVI, 1121 p. 435 illus., 390 illus. in color.